The Role of the Kenyan Diaspora in Constructing a New Political Culture and Identity - Eric Masinde Aseka (Journal of Global Initiatives, 2010)
This paper focuses on the need for and the prospects of a congenial politics of identity construction in Kenya as spearheaded by the country's diasporic communities. It identifies and interrogates the intersection of consciousness and historical experience as the basis of such identity construction. It posits the leadership function as a critical component in this process and points out how mismanagement of the African polity has led to swelling ranks of refugees. These émigrés have contributed to the making of a global Africa embodied in the Black Diaspora. This diaspora can help reconstruct the politics of identity within Kenya as it diagnoses and explores cultural logics of power informing national politics.